Design and Development of Solar/LPG powered Areca-nut leaf Plate Press Machine and Areca Leaf Sheath-Solar dryer. (2018) - Nikhil, R.; Raahul, N.; Sateesh, N.; Shivpriyan, M.; Clein, Tiffany; Tang, Anita; Pramod, R.
Abstract: The whole idea is to produce eco-friendly plates from the sheaths of the Areca palm tree leaves. The technology developed for and employed in the project has negated the issues of production challenges that occurred due to humid weather conditions, high cost machines and low quality and fungus prone products. We have ergonomically designed the press machine. The dried sheaths are placed inside the machine using the required die size to manufacture plates and bowls of different sizes. The upper die plate made of aluminium is heated using electricity. Then the sheath is placed on the lower die and will be pressed against the upper die to create plate. In order to remove moisture content, we have designed an indirect forced convection Solar dryer. With integrated cutters in die, a separate cutter mechanism is avoided to prevent reduction of sheath waste. The most distinguished achievement of the project lies in its ability to develop entrepreneurial spirit among the rural unemployed youth, by providing them a dignified livelihood generation activity. Further the current technology will ensure to produce plates at a cost of 1 rupee which is way less than banana leaf. Most of the existing machines are costly in nature and they range from 1.5 lakhs to 3 lakh rupees. Further most of these machines lack a drying chamber. The initiative boosts the growth of palm trees ensuring year round employment and women empowerment leading towards creation of a self-sustained rural economic model.